Foreign Banks : Trends, Impact and Financial Stability - Horen, Neeltje; Claessens, Stijn (Washington, D.C. : International Monetary Fund, 2012)
This paper introduces a comprehensive database on bank ownership for 137 countries over 1995-2009, and reviews foreign bank behavior and impact. It documents substantial increases in foreign bank presence, with many more home and host countries. Current market shares of foreign banks average 20 percent in OECD countries and 50 percent elsewhere. Foreign banks have higher capital and more liquidity, but lower profitability than domestic banks do. Only in developing countries is foreign bank presence negatively related with domestic credit creation. During the global crisis foreign banks reduced credit more compared to domestic banks, except when they dominated the host banking systems.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet